OS IMPACTOS JURÍDICOS E SOCIAIS DAS FAKE NEWS EM TERRITÓRIO BRASILEIRO (Reflection and Critique Law Magazine, 2020)
Fake news has a great impact on the population, due to its peculiar characteristics, the 2018 Brazilian election, especially with regard to the presidential campaign, had a great occurrence of fake news that were widely shared on social networks, such as Facebook, Whatsapp and Twitter, however, the main disseminator of these fake news, without a doubt, was the WhatsApp messaging application. Due to this large amount of lying material that was disseminated, the Superior Electoral Court had to take some actions and remove certain fake news from circulation. This great accumulation of untrue news has generated a change both in behavior and in the opinion of society in general, which starts to believe in what it sees immediately, leaving aside its source and not going to research the subject, to know if in fact it is true or a lie. When analyzing the 2018 election and verifying the effects that fake news produced, both in the legal sphere and in society, it would be natural to expect to find a possible answer from a medium that the Superior Electoral Court or even the very The Supreme Federal Court could have taken it so that it would not reach the point of having a flood of false news being passed on and passed on by the thousands every day.